Image-Based Differentiation of Benign and Malignant Peripheral Nerve Sheath Tumors in Neurofibromatosis Type 1 - Liu, Jun; Huang, Jing-Ning; Wang, Ming-Han; Ni, Zhen-Yang; Jiang, Wei-Hao; Chung, Manhon; Wei, Cheng-Jiang; Wang, Zhi-Chao (Frontiers in Oncology, 2022)
Neurofibromatosis type 1 (NF1) is a dominant hereditary disease characterized by the mutation of the NF1 gene, affecting 1/3000 individuals worldwide. Most NF1 patients are predisposed to benign peripheral nerve sheath tumors (PNSTs), including cutaneous neurofibromas (CNFs) and plexiform neurofibromas (PNFs). However, 5%-10% of PNFs will ultimately develop into malignant peripheral nerve sheath tumors (MPNSTs), which have a poor prognosis. Early and reliable differentiation of benign and malignant tumors in NF1 patients is of great necessity. Pathological evaluation is the “gold standard” for a definite diagnosis, but the invasive nature of the biopsy procedure restricts it from applying as a screening tool during the decades-long follow-up of these patients. Non-invasive image-based diagnostic methods such as CT and MRI are often considered essential screening tools for multiple types of tumors. For NF1 patients’ lifelong regular follow-ups, these radiological methods are currently used for tumor evaluation. However, no consensus was established on screening the malignant transformation of benign PNSTs. Moreover, novel technologies like radiogenomics and PET-MRI have not been well evaluated and fully adopted for NF1 patients. This review summarizes current studies of different imaging methods for differentiating benign and malignant tumors in NF1. Meanwhile, we discussed the prospects of the usage of new tools such as radiogenomics and PET-MRI to distinguish MPNST from benign PNSTs more precisely. Summarizing these findings will help clarify the directions of future studies in this area and ultimately contribute to the radiology images-based clinical screening of MPNST in NF1 patients and finally improve the overall survival rates of these patients.